Graphite radiating fin with multi-layer composite structure and manufacturing process of graphite radiating fin
Through the graphite heat sink with a multi-layer composite structure, graphene oxide, artificial graphite powder and other components are used to form a continuous thermal conductivity network, which solves the problems of improved thermal conductivity and insufficient stability of existing carbon-based materials, and achieves efficient thermal conductivity and material stability.
Patent Information
- Application Number
- CN202510441563.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-09
- Publication Date
- 2025-07-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the process of improving thermal conductivity, existing carbon-based materials have problems such as insufficient interface regulation, thermal aging and structural degradation, and inorganic nanoparticles are difficult to form synergistic effects on the microstructure, resulting in insufficient optimization of material stability and heat flow channel.
A graphite heat sink with a multi-layer composite structure is used to form a continuous thermal conductivity network through the combination of graphene oxide, artificial graphite powder, aniline-p-phenylenediamine copolymer, antimony oxide nanoparticles, urea and polyvinylpyrrolidone, and aniline-p-phenylenediamine copolymer to form a phonon bridge structure. The urea is nitrogen doped, and polyvinylpyrrolidone improves dispersion and bonding, while aniline-p-phenylenediamine copolymer improves thermal conductivity.
It significantly improves the lateral thermal conductivity of the membrane body, improves the heat diffusion ability, achieves more stable thermal conductivity, avoids the problems of material embrittlement and unstable thermal conductivity, and improves the stability of the material in high-temperature environments.
Smart Images

Figure CN120289184A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of heat dissipation materials, and particularly to a graphite heat sink with a multi-layer composite structure and a manufacturing process thereof. Background Art
[0002] With the increasing demand for thermal management in electronic devices and industrial equipment, thermal conductive materials play an increasingly important role in modern technology. Especially in the fields of electronic heat dissipation, energy conversion, etc., how to improve the performance of thermal conductive materials and reduce energy loss has become a research hotspot. Traditional thermal conductive materials, such as metals or carbon-based materials, are difficult to meet the increasingly complex requirements of efficient thermal management due to their inherent thermal conductivity limitations in many cases.
[0003] Existing carbon-based materials are widely used in various thermal conductive devices due to their excellent thermal conductivity. Especially in the fields of electronic heat sinks, thermal interface materials (TIM), etc., carbon-based materials such as carbon nanotubes and graphene are widely used as additives or matrices. In addition, some inorganic nanoparticles (such as antimony oxide, aluminum, silicon, etc.) are also used to enhance the thermal conductivity of materials. Composite schemes of various materials have been proposed and applied in actual production, aiming to improve the overall thermal conductivity by optimizing the interface effect and material distribution.
[0004] However, existing component composite materials usually rely on physical mixing or simple chemical doping, but the interfaces between materials are not precisely regulated, resulting in difficult smooth passage of heat flow through the materials. Secondly, many thermal conductive materials are prone to thermal aging or structural degradation due to high temperature or long-term use while the thermal conductivity is improved, thus affecting the stability of the materials. Moreover, additives in the existing technology (such as inorganic nanoparticles) are difficult to effectively form a synergistic effect in the microstructure, and many methods rely only on a single enhancement path, lacking systematic optimization of the overall layout of the heat flow channels. Therefore, the present invention provides a graphite heat sink with a multi-layer composite structure and a manufacturing process thereof to solve the deficiencies existing in the prior art. Summary of the Invention
[0005] Aiming at the deficiencies of the prior art, the present invention provides a graphite heat sink with a multi-layer composite structure and a manufacturing process thereof, which solves the problems of deficiencies in improving the thermal conductivity, material stability, and structural optimization of existing materials.
[0006] To achieve the above objectives, the present invention is realized through the following technical solutions: A graphite heat sink with a multi-layer composite structure, comprising the following components in parts by weight: Graphene oxide: 30 - 45 parts; Artificial graphite powder: 15 - 25 parts; Aniline-p-phenylenediamine copolymer: 3 - 8 parts; Antimony oxide nanoparticles: 2 - 6 parts; Urea: 2 - 5 parts; Polyvinylpyrrolidone: 1 - 3 parts; Mixed solvent: 100 - 150 parts.
[0007] Graphene oxide: 30 - 45 parts; Graphene oxide serves as the basic constituent material. After exfoliation, it forms a two - dimensional sheet structure with a high specific surface area and high in - plane thermal conductivity. This structure constructs the main in - plane thermal conduction network in the heat dissipation film, helping to efficiently conduct heat flux. The micro - scale size of the graphene oxide sheets is between nanometers and micrometers, with good flexibility and stacking ability, suitable for forming a continuous thermal conduction film body.
[0008] Artificial graphite powder: 15 - 25 parts; Artificial graphite powder is an auxiliary reinforcing filler with a particle size of 5 - 15μm. It has a natural layered graphite structure and can be filled in the void areas between graphene oxide sheets, improving the integrity of the thermal conduction network of the film body and enhancing the mechanical structure of the film layer. Due to its sheet structure having good structural compatibility with graphene oxide, it can synergistically construct in - plane heat conduction paths during heat treatment and rolling processes, thus forming a micro - nano - scale multi - scale composite heat conduction structure.
[0009] Aniline - p - phenylenediamine copolymer: 3 - 8 parts; Aniline - p - phenylenediamine copolymer is a polymer bridging agent rich in aromatic ring structures. It can be adsorbed on the surface of graphene oxide through π - π stacking interactions and connect multiple sheets or graphite particles. Its molecular chains can be carbonized during heat treatment to form an intermediate interface layer, thereby improving the thermal conduction continuity between sheets. This copolymer also has a certain degree of flexibility, helping to maintain the integrity and deformability of the film body during film formation and rolling stages.
[0010] Antimony oxide nanoparticles: 2 - 6 parts; The particle size of antimony oxide nanoparticles is 20 - 30nm. They can be evenly dispersed in the slurry and interspersed between graphene oxide and graphite powder. Their main function is to construct a "phonon bridging" structure. These inorganic particles have a high phonon propagation rate and can form a phonon continuous transition region at the hetero - interface, thereby reducing the interface thermal resistance caused by lattice mismatch and increasing the inter - layer heat flux. In addition, they can stably exist inside the film body after high - temperature treatment and are not easily migrated or decomposed.
[0011] Urea: 2 - 5 parts; Urea serves as a doping source. During high - temperature carbonization, it releases ammonia and small - molecule intermediate products, enabling nitrogen atom doping in carbon materials. The introduction of nitrogen atoms can, on the one hand, regulate the electron density of the carbon lattice and improve the conductivity structure, and on the other hand, induce a slight rearrangement between graphene layers at the microscopic level, thereby promoting the alignment and stability of its sheets. This type of nitrogen - doped configuration has a positive effect on enhancing the coupling of the overall thermal conduction network.
[0012] Polyvinylpyrrolidone: 1 to 3 parts; As a dispersant and binder assistant, polyvinylpyrrolidone mainly functions to stabilize the dispersion of each component during the pulping stage, prevent particle agglomeration, and improve coating uniformity. At the same time, it can form a flexible connection network during the drying and heat treatment processes, enhance the interlayer bonding force, and avoid problems such as fracture or detachment of the film layer during peeling or rolling. In addition, its thermal decomposition products also have a certain auxiliary carbonization effect on the overall carbon structure.
[0013] Mixed solvent: 100 to 150 parts; The mixed solvent is composed of ethanol and deionized water mixed in a volume ratio of 1:1. It can not only provide an appropriate dissolution polarity to disperse polar components such as GO and PVP, but also has a relatively low evaporation temperature, facilitating rapid removal in the subsequent drying step. The balanced design of the solvent ratio is beneficial to stabilizing the rheological properties of the slurry system and ensuring uniform thickness and dense surface during the film layer formation process.
[0014] Preferably, the graphene oxide is a two-dimensional structural material with a sheet diameter of 1 to 5 μm and a thickness less than 2 nm.
[0015] Preferably, the particle size of the artificial graphite powder is 5 to 15 μm, and the particle size of the antimony oxide nanoparticles is 20 to 30 nm.
[0016] Preferably, the mixed solvent is a mixture of ethanol and deionized water with a volume ratio of 1:1, and the heat dissipation film is formed into a laminated structure by rolling.
[0017] Also provided is a preparation method of a graphite heat dissipation sheet with a multi-layer composite structure, including the following steps: Heat-treat the artificial graphite film and then mechanically crush it to obtain artificial graphite powder with a particle size of 5 to 15 μm; Mix graphene oxide with an ethanol or water mixed solvent containing ammonia water, stir evenly, and perform primary exfoliation at 50 to 70 °C to obtain a graphene oxide slurry; Mix the artificial graphite powder, graphene oxide slurry, aniline-p-phenylenediamine copolymer, antimony oxide nanoparticles, urea, and polyvinylpyrrolidone, stir evenly, and perform secondary exfoliation at 60 to 80 °C to form a composite slurry; Perform vacuum degassing on the composite slurry, then coat it on a substrate, dry it and peel it to obtain a crude graphene film; Carbonize the crude graphene film in an inert atmosphere at 300 to 450 °C; Graphitize the carbonized film in an inert atmosphere at 1800 to 2200 °C; Perform lamination rolling on the graphitized film to form the final product.
[0018] The artificial graphite film is heat-treated and then mechanically pulverized to obtain artificial graphite powder with a particle size of 5 - 15 μm; The original structure of the artificial graphite film is dense and it is difficult to directly fuse with other materials. The heat treatment step can pre-induce the loosening of the graphite layer structure, which helps with subsequent physical dissociation and powder homogenization. The pulverized graphite powder retains part of the ordered stacking structure and can serve as a heat conduction skeleton conduction path during the subsequent film-making process, improving the in-plane thermal conductivity of the final film.
[0019] Graphite oxide is mixed with an ethanol or water mixed solvent containing ammonia water, stirred evenly, and then subjected to primary exfoliation at 50 - 70 °C to obtain graphene oxide slurry; Ammonia water can partially reduce the surface carboxyl groups of GO under alkaline conditions, making it easier to exfoliate into single-layer or few-layer graphene structures. At the same time, the shear force provided by ultrasonic waves promotes the uniform exfoliation of GO in the liquid phase, thus forming a stable slurry system. This slurry has high lamellar dispersibility, providing a basis for the subsequent construction of a layer-by-layer stacked film structure.
[0020] The artificial graphite powder, graphene oxide slurry, aniline-p-phenylenediamine copolymer, antimony oxide nanoparticles, urea, and polyvinylpyrrolidone are mixed, stirred evenly, and then subjected to secondary exfoliation at 60 - 80 °C to form a composite slurry; PDA has the ability of π-π stacking, which can induce the formation of an ordered stack between GO lamellae and provide partial flexible interface regulation; antimony oxide nanoparticles, as inorganic bridging agents, can form phonon coupling bridges at the interface between GO and graphite powder, reducing the interface thermal resistance; urea, as a doping source, can induce nitrogen doping during subsequent heat treatment, improving the electrical and thermal conductivity of the carbon phase; PVP enhances the dispersion stability of the system and prevents sedimentation. The entire mixed system finally presents a good structural basis for micro-assembly.
[0021] The composite slurry is subjected to vacuum degassing and then coated on a substrate, dried and peeled off to obtain a crude graphene film; The degassing operation is a key step to ensure the density of the film. If microbubbles remain, they will form thermal resistance points and reduce the thermal conductivity; the PI film provides high-temperature stability as a temporary substrate. The solvent is gradually removed during the drying process to avoid film cracking or shrinking; the thickness control formed by doctor blading directly determines the balance between the thermal resistance and flexibility of the heat dissipation film.
[0022] The crude graphene film is carbonized at 300 - 450 °C in an inert atmosphere; The carbonization treatment can decompose organic components such as PVP and PDA into a carbon skeleton, while retaining some defect sites to form a porous but interconnected heat conduction structure, which helps to construct a uniform heat flow channel and lays a structural foundation for subsequent graphitization.
[0023] The carbonized film is graphitized in an inert atmosphere at 1800 - 2200 °C; High-temperature induces restacking between GO and artificial graphite and graphitization reconstruction, significantly enhancing the orderliness of the lamellae. Heteroatoms (such as nitrogen) are stably doped to form C-N bonds at this stage, improving the in-plane phonon migration efficiency, and finally forming a continuous carbon crystal network structure.
[0024] The graphitized film is subjected to laminating and rolling to form the final product; Rolling can significantly improve the in-plane alignment degree of GO lamellae. At the same time, it compacts the micropores and gaps between multiple layers, reducing the contact thermal resistance. Hot pressing induces redistribution of each functional component, contributing to interface reconstruction and overall thermal network penetration, which is the key process to achieve excellent thermal conductivity and film flexibility.
[0025] Preferably, the vacuum degree for vacuum degassing is -0.08 to -0.1 MPa, and the degassing time is 20 - 40 minutes.
[0026] Preferably, the drying treatment includes two-stage temperature-controlled drying. The temperature in the first stage is 80 - 100 °C, the temperature in the second stage is 100 - 150 °C, and the total time is 20 - 40 minutes.
[0027] Preferably, the heat preservation time for carbonization treatment is 0.5 - 1 hour, and the heat preservation time for graphitization treatment is 1 - 2 hours.
[0028] Preferably, the pressure for rolling treatment is 15 - 30 MPa, and the temperature is 80 - 150 °C.
[0029] Preferably, the substrate is a polyimide film with a thickness of 10 - 50 μm.
[0030] The present invention provides a graphite heat sink with a multi-layer composite structure and its manufacturing process. It has the following beneficial effects: 1. The present invention adopts the technical scheme of using antimony oxide nanoparticles to synergistically regulate the thermal conductivity, achieving the effect of significantly improving the in-plane thermal conductivity of the film. Compared with the pure carbon-based material scheme in the prior art, by introducing antimony oxide into the carbon film, the present invention not only enhances the heat conduction ability but also avoids material embrittlement caused by excessive filling, solving the problem of limited improvement in thermal conduction efficiency in the traditional scheme.
[0031] 2. The present invention adopts the technical scheme of using nitrogen doping to regulate the microstructure of the carbon film, successfully improving the thermal diffusion ability of the film. Compared with the traditional inorganic doping technology, by precisely controlling the nitrogen source ratio, the present invention enables heat conduction not to be limited to a single path, breaking through the limitations of single improvement in thermal conductivity and great difficulty in structural optimization in the past.
[0032] 3. By combining the cross-linking enhancement technology of PDA copolymer and carbon materials, the present invention optimizes the thermal conduction network structure of the membrane body, achieving more stable thermal conductivity performance. Compared with the single-substance enhancement scheme in the prior art, the present invention effectively avoids the problems of unstable thermal conductivity and incomplete reaction, and realizes the improvement of thermal conductivity performance in a large range.
[0033] 4. The present invention adopts a technical solution of regulating the thermal conductivity of carbon film materials through the multi-component synergistic effect, overcoming the deficiencies of poor material stability and limited thermal conductivity improvement in traditional technologies. By reasonably adjusting the doping ratios of copolymer, nanoparticles and nitrogen source, the present invention makes the synergistic effect of different components more obvious, effectively improves the thermal conductivity performance of the overall membrane body, and ensures its stability in high-temperature environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a flow chart of the preparation method of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0035] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.
[0036] Please refer to the attach Figure 1 , Example 1: Raw material components (by mass fraction): 40 parts of graphene oxide; 20 parts of artificial graphite powder; 5 parts of aniline-p-phenylenediamine copolymer (PDA copolymer); 3 parts of antimony oxide nanoparticles; 4 parts of urea; 2 parts of polyvinylpyrrolidone (PVP); 120 parts of mixed solvent (ethanol / deionized water, volume ratio 1:1).
[0037] Preparation steps: Step S1. Preparation of graphene oxide slurry: Weigh 40 parts of graphene oxide, add it to 120 parts of mixed solvent (the volume ratio of ethanol and deionized water is 1:1), stir for 10 minutes for pre-dispersion, place the mixture in a water bath at 60°C for ultrasonic treatment, and continue to exfoliate for 45 minutes to obtain a stable GO slurry.
[0038] Step S2. Integration of mixed components: Add 4 parts of urea and 2 parts of PVP to the GO slurry, and continue stirring for 15 minutes. Then, sequentially add 20 parts of artificial graphite powder, 5 parts of aniline-p-phenylenediamine copolymer, and 3 parts of antimony oxide nanoparticles, and maintain the stirring temperature at 70 °C for 40 minutes.
[0039] Step S3, degassing treatment: Degas the above composite slurry under a vacuum condition of –0.09 MPa for 30 minutes.
[0040] Step S4, coating and drying: Evenly scrape the degassed slurry onto the PI film, and control the scraping film thickness at 45 μm. The drying is divided into two stages: the first stage is set at 80 °C for 10 minutes; the second stage is raised to 120 °C and dried for 25 minutes. After the dry film is cooled to room temperature, gently peel off the base film.
[0041] Step S5, carbonization and graphitization: Place the peeled film in a nitrogen atmosphere, heat it to 350 °C, and keep it for 1 hour for carbonization treatment. After cooling, heat it up to 2000 °C again and perform graphitization treatment for 1.5 hours under an inert atmosphere to obtain a black flexible film.
[0042] Step S6, calendering and forming: Place the film into a double-roll hot pressing device, set the temperature at 120 °C, the pressure at 25 MPa, and control the calendering speed at 1 m / min. After calendering, cool and wind up to obtain the final heat dissipation film.
[0043] Example 2: Raw material components (by mass fraction): 36 parts of graphene oxide; 25 parts of artificial graphite powder; 6 parts of aniline-p-phenylenediamine; 4 parts of antimony oxide nanoparticles; 5 parts of urea; 2 parts of polyvinylpyrrolidone (PVP); 140 parts of mixed solvent (ethanol / deionized water, volume ratio 1:1).
[0044] Preparation steps: Step S1, preparation of graphene oxide slurry: Take 36 parts of GO and add it to 140 parts of the mixed solvent, control the temperature at 55 °C, and the ultrasonic treatment time at 40 minutes. After a stable slurry is formed, let it stand for 5 minutes.
[0045] Step S2, integration of mixed components: First, add 5 parts of urea to the GO system and stir evenly. Subsequently, add 25 parts of graphite powder, 6 parts of PDA copolymer, and 4 parts of antimony oxide all at once, and raise the stirring temperature to 75 °C and maintain stirring for 60 minutes.
[0046] Step S3, degassing treatment: The mixed slurry is degassed under a vacuum condition of –0.1 MPa for 25 minutes. After degassing, the color of the slurry is dark brown and the consistency is moderate.
[0047] Step S4, coating and drying: The blade coating thickness is set to 50 μm, and the slurry is evenly applied. The drying process is 10 minutes at 85 °C, followed by 20 minutes at 130 °C.
[0048] Step S5, carbonization and graphitization: The film body is first carbonized in nitrogen, the temperature is set to 400 °C, and the heat preservation time is 48 minutes. After cooling, it enters the second-stage graphitization and is treated at 2100 °C for 1 hour.
[0049] Step S6, calendering and forming: The hot pressing conditions of the film body are set to 100 °C and the pressure is 20 MPa. The calendering is completed in one pass, and finally a graphene heat dissipation film is obtained.
[0050] Example 3: 38 parts of graphene oxide; 18 parts of artificial graphite powder; 8 parts of aniline-p-phenylenediamine copolymer (PDA copolymer); 6 parts of antimony oxide nanoparticles; 3 parts of urea; 3 parts of polyvinylpyrrolidone (PVP); 130 parts of mixed solvent (ethanol / deionized water, volume ratio 1:1).
[0051] Preparation steps: Step S1, preparation of graphene oxide slurry: Add 38 parts of graphene oxide to 130 parts of mixed solvent, set the water bath temperature to 60 °C, and the ultrasonic time is 35 minutes.
[0052] Step S2, integration of mixed components: Add 3 parts of urea and 3 parts of PVP and stir for 10 minutes. Then add 18 parts of artificial graphite powder, 8 parts of PDA, and 6 parts of antimony oxide particles, and continue stirring for 50 minutes.
[0053] Step S3, degassing treatment: Place the mixed system in a degassing tank, the vacuum degree is –0.085 MPa, the time is 35 minutes, and terminate when the bubble discharge is significantly weakened.
[0054] Step S4: Coating and Drying The scraping film thickness of the slurry is controlled at 40 μm and applied to the PI film. The drying temperature in the first stage is 90 °C for 15 minutes; in the second stage, it is raised to 140 °C and dried for another 15 minutes.
[0055] Step S5: Carbonization and Graphitization The carbonization treatment temperature is 320 °C and held for 30 minutes; for graphitization, it is heated to 1900 °C and held for 2 hours.
[0056] Step S6: Calendering and Forming The film material is placed in a hot pressing device with a calendering temperature of 110 °C, a pressure of 30 MPa, and a speed of 1.2 m / min.
[0057] Comparative Example 1 Compared with Example 1, the difference is that the PDA copolymer is not added, and the rest are the same.
[0058] Comparative Example 2 Compared with Example 2, the difference is that the mass fraction of urea is reduced from 5 parts to 1 part, and the rest are the same.
[0059] Comparative Example 3 Compared with Example 3, the difference is that the antimony oxide nanoparticles are removed, and the rest are the same.
[0060] Experiment 1: Verification Experiment on the Regulation Effect of PDA Copolymer on Interface Thermal Resistance Experimental Purpose: To evaluate whether the aniline-p-phenylenediamine copolymer (PDA) can significantly reduce the interface thermal resistance in the vertical heat conduction path and improve the vertical thermal conductivity performance after forming a synergistic bridging network in the film structure.
[0061] Experimental Steps (Three Experiments): Sample Preparation: Prepare the composite films corresponding to Example 1 and Comparative Example 1 respectively, ensure that other ratios and process parameters (drying temperature, heat treatment, calendering) are the same, and the final thickness of the film body is uniformly calendered to 30 μm and cut into 10 mm × 10 mm square samples.
[0062] Thermal Conductivity Test (Laser Flash Method LFA): Each sample is measured 3 times, and the temperature points are set at 25 °C, 60 °C, and 100 °C. Record the thermal diffusivity and calculate the vertical thermal conductivity (combining density and specific heat).
[0063] Auxiliary Analysis of Interface Synergistic Structure: Test the N element signal of the sample to evaluate the residue and chemical state of PDA in the structure.
[0064] The experimental results are shown in Table 1: Table 1: Experimental Data on the Influence of the Introduction of PDA Copolymer on Vertical Thermal Conductivity Experimental summary: By introducing a polydopamine (PDA) modification layer, the composite material system exhibits significant nitrogen element doping characteristics. It is confirmed by XPS detection that the concentration of interfacial active groups has increased by more than 37%. Microstructural observation shows that the internal phase distribution morphology of the material has changed from the initial discrete island-like structure to a three-dimensional interpenetrating network structure, where the PDA interfacial bridging layer promotes the formation of chemical bonding connections between the filler and the matrix.
[0065] In the vertical orientation thermal conduction test, the modified sample shows a breakthrough thermal conductivity enhancement effect: the thermal conductivity at room temperature has increased by 152 ± 5%, exceeding the expected value of the conventional physical blending system; a plateau effect appears in the characteristic temperature range (60 - 100 °C), confirming the unique thermal stability of the PDA interfacial phase; it is found through time-domain thermoreflectance (TDTR) detection that the interfacial thermal resistance has been reduced to 1 / 8 of the original system.
[0066] This PDA modification technology maintains a stable thermal bridge effect in the temperature range of 60 - 180 °C; a chemical bonding interface is formed through in-situ polymerization, avoiding the thermal degradation risk of traditional coupling agents; the formation of the amorphous transition layer enables the material to have both high thermal conductivity and thermal shock resistance (the performance attenuation is < 3% after 100 thermal cycling).
[0067] Experiment 2: Verification experiment on the influence of nitrogen source doping ratio on the lattice order and thermal properties of carbon film. Experimental purpose: To explore the effect of urea ratio on the regulation of lattice defects of graphite carbon film, and to evaluate the specific influence trend of different nitrogen contents on the lateral thermal conductivity, so as to confirm the effectiveness and limitations of the nitrogen source adjustment strategy.
[0068] Experimental procedure (second experiment): Film preparation: Prepare the film strictly according to the formulations of Example 2 and Comparative Example 2. Other components and processes are the same, only the urea dosage is different (5 parts vs 1 part). All samples are uniformly calendered to a thickness of 45 μm, and the drying temperature is set at 85 °C + 130 °C.
[0069] Raman spectroscopy test: Use a 532 nm laser, scan range 800–2000 cm -1 , obtain the intensities of the D peak and the G peak, and calculate the ID / IG ratio. Each sample is tested at 5 different positions, and the average value is taken, and the standard deviation is recorded.
[0070] XRD test: Detect changes in crystal spacing, interlayer structure and crystallinity, and analyze the influence of urea on the carbon phase stacking behavior.
[0071] Lateral thermal conductivity test: Use a thermal constant analyzer to test the lateral thermal conductivity, and each sample is tested 2 times.
[0072] The experimental results are shown in Table 2: Table 2: Data on the influence of nitrogen doping ratio on the film structure and thermal conductivity performance Experimental summary: When the doping concentration is reduced to a certain extent, the overall film structure shows a relaxed state, and obvious structural gaps appear between the originally closely arranged carbon layers. Although no obvious fracture surface is observed, the arrangement of carbon layers tends to be non-periodic, and the structural stability decreases. In the Raman spectroscopy test, the ID / IG ratio increases significantly, indicating an increase in the defect density, and the D peak signal becomes the main feature. The transverse heat conduction performance shows obvious hysteresis in the structural defect area, playing a heat barrier effect, similar to introducing a flexible heat-resistant medium between layers.
[0073] During the material preparation process, further increasing the urea addition does not directly fill the voids in the film structure, but shows an indirect regulatory effect on the microstructure of the material. Urea promotes the formation of more heteroatom doping sites in reduced graphene oxide (rGO) during the heat treatment stage. This process not only introduces nitrogen elements but also enhances the uniformity of the distribution of heteroatoms in the film. The experimental results show that a high urea concentration induces the formation of a more compact interlayer stacking structure, and this stacking trend has a certain degree of self-organization characteristics rather than simply geometric repetitive stacking.
[0074] Experiment 3: Verification experiment on the synergistic effect of inorganic nanoparticles on improving the thermal conductivity of the film Experimental purpose: To verify whether the introduction of antimony oxide (Sb2O3) nanoparticles can form a synergistic heat conduction network structure in the carbon-based film, assist in constructing a more complete heat conduction path, and improve the overall thermal conductivity.
[0075] Experimental steps: Sample preparation: Prepare the films of Example 3 and Comparative Example 3, the difference being whether 5 parts of antimony oxide nanoparticles are added. The thickness of the two groups of films is uniformly controlled at 40 μm, and all heat treatment and rolling conditions are the same.
[0076] Thermal conductivity test (TPS): Measure the transverse thermal conductivity. Each group of samples is measured 3 times, and the average value is recorded, paying attention to the change range of thermal conductivity.
[0077] Thermal response imaging: Record the surface temperature rise process of the sample under electric heating. Set the power to 0.5 W, and record the maximum surface temperature rise value at 30 seconds, which is used as a comparison index for the thermal diffusion ability.
[0078] Data assistance: Test the density and specific heat capacity of the samples to verify the consistency of thermal conductivity calculation.
[0079] The experimental results are shown in Table 3: Table 3: Data on the influence of antimony oxide addition on thermal conductivity and thermal diffusion ability Experimental summary: The introduction of antimony oxide (Sb2O3) nanoparticles can form a multi-path collaborative heat conduction network in the carbon-based film body, effectively improving the lateral thermal conductivity of the film body. Although antimony oxide is not the main framework material of the film body, its distribution in the film structure has a high degree of freedom and is mainly distributed in the microscopic gap regions between carbon layers. This type of distribution state helps to form auxiliary heat conduction channels and reduce the interfacial thermal resistance during the lateral transmission of heat flux.
[0080] The thermal conductivity test data shows that the average thermal conductivity of the sample with antimony oxide added in Example 3 is significantly higher than that of Comparative Example 3 without addition, indicating that this additive has a positive regulatory effect on the thermal conductivity of the film body. At the same time, the results of thermal response infrared imaging also show that the maximum surface temperature rise of the sample with antimony oxide added after 30 seconds of power-on is higher than that of the comparative example, further verifying the improvement of its thermal diffusion efficiency.
[0081] It should be noted that although the overall thermal conductivity shows an increasing trend, some test data have a certain degree of non-linear fluctuation. This phenomenon is presumably related to the non-uniform and random distribution state of antimony oxide nanoparticles in the carbon-based film body, resulting in the non-uniform self-organization reconstruction of the local heat channel structure. The resulting collaborative heat conduction network has a certain degree of instability and spatial distribution difference.
[0082] Although the embodiments of the present invention have been shown and described, for those of ordinary skill in the art, it can be understood that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A graphite heat sink with a multi-layer composite structure, characterized in that, Comprising the following components in parts by weight: Graphene oxide: 30 - 45 parts; Artificial graphite powder: 15 - 25 parts; Aniline - p - phenylenediamine copolymer: 3 - 8 parts; Antimony oxide nanoparticles: 2 - 6 parts; Urea: 2 - 5 parts; Polyvinylpyrrolidone: 1 - 3 parts; Mixed solvent: 100 - 150 parts.
2. The graphite heat sink with a multi-layer composite structure according to claim 1, characterized in that, The graphene oxide is a two - dimensional structural material with a sheet diameter of 1 - 5 μm and a thickness less than 2 nm.
3. The graphite heat sink with a multi-layer composite structure according to claim 1, characterized in that, The particle size of the artificial graphite powder is 5 - 15 μm, and the particle size of the antimony oxide nanoparticles is 20 - 30 nm.
4. The graphite heat sink with a multi-layer composite structure according to claim 1, characterized in that, The mixed solvent is a mixture of ethanol and deionized water with a volume ratio of 1:1, and the heat - dissipating film is formed into a laminated structure by calendering.
5. A method for preparing a graphite heat sink with a multi-layer composite structure, which is applied to the graphite heat sink with a multi-layer composite structure described in any one of claims 1-4, and is characterized in that, Including the following steps: Heat - treat the artificial graphite film and then mechanically crush it to obtain artificial graphite powder with a particle size of 5 - 15 μm; Mix graphite oxide with an ethanol or water mixed solvent containing ammonia water, stir evenly, and perform primary exfoliation at 50 - 70 °C to obtain graphene oxide slurry; Mix the artificial graphite powder, graphene oxide slurry, aniline - p - phenylenediamine copolymer, antimony oxide nanoparticles, urea, and polyvinylpyrrolidone, stir evenly, and perform secondary exfoliation at 60 - 80 °C to form a composite slurry; Perform vacuum degassing on the composite slurry, then coat it on a substrate, perform drying treatment and peeling to obtain a crude graphene film; Carbonize the crude graphene film in an inert atmosphere at 300 - 450 °C; Graphitize the carbonized film in an inert atmosphere at 1800 - 2200 °C; Perform laminated calendering treatment on the graphitized film to form the final product.
6. The preparation method of a graphite heat sink with a multi-layer composite structure according to claim 5, characterized in that, The vacuum degree of the vacuum degassing is - 0.08 - - 0.1 MPa, and the degassing time is 20 - 40 minutes.
7. The preparation method of a graphite heat sink with a multi-layer composite structure according to claim 5, characterized in that, The drying treatment includes two - stage temperature - controlled drying. The temperature in the first stage is 80 - 100 °C, the temperature in the second stage is 100 - 150 °C, and the total time is 20 - 40 minutes.
8. A method for preparing a graphite heat sink with a multi-layer composite structure according to claim 5, characterized in that, The heat - preservation time of the carbonization treatment is 0.5 - 1 hour, and the heat - preservation time of the graphitization treatment is 1 - 2 hours.
9. The preparation method of a graphite heat sink with a multi-layer composite structure according to claim 5, characterized in that The pressure of the calendering treatment is 15 - 30 MPa, and the temperature is 80 - 150 °C.
10. The preparation method of a graphite heat sink with a multi-layer composite structure according to claim 5, characterized in that, The substrate is a polyimide film with a thickness of 10 - 50 μm.
Citation Information
Cited By
Preparation method of high-heat-transfer graphite-based interface material
CN121798987A
Preparation method of composite graphite sagger for sintering lithium manganese iron phosphate positive electrode material
CN122212754A